Health care practitioners’ perceptions of transdermal therapeutic systems in Palestinian territories - Naser, Zaid Abdel (Asian Journal of Pharmaceutics (AJP), 2014)
To evaluate the scientific knowledge and attitudes of health professionals in Palestine regarding the advantages of transdermal therapeutic systems (TTSs) over conventional therapy. Data were gathered from a questionnaire that was handed out to community pharmacists and physicians. Pharmaceutical industry decision makers were enrolled in this study. Data were analyzed using the SPSS statistical software program version 10. 79.5% of pharmacists and 74% of physicians thought that TTSs eliminate variables due to gut absorption. 78.8% of pharmacists and 65.6% of physicians were in agreement regarding the capacity of TSs to avoid first-pass metabolism. In this study, 83.3% of the physicians and 81.3% pharmacists T still agree that TTSs may provide controlled release. 55.8% of pharmacists and only 26% of physicians believed that TTSs eliminate drug-plasma fluctuation. 56.8% of pharmacists and 63.5% of physicians agreed that TTSs can use drugs with low therapeutic indices. 81.3% of pharmacists and 85.4% of physicians believed that TTSs are not invasive and can be removed easily to stop drug administration. 81.3% of physicians and 89.1% of pharmacists thought that TTSs may irritate or sensitize the skin. Eighty-four percent of pharmacists and 75% of physicians recognize that TTSs should contain drugs that must be stable and have correct physicochemical properties. The importance of TSs is understood and appreciated by Palestinian T health personnel. Pharmaceutical industries should pay more attention to the development and production of TSs due to T the valuable advantages of this therapeutic system.